2008
DOI: 10.1111/j.1365-294x.2007.03668.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA reveals multiple Northern Hemisphere introductions of Caprella mutica (Crustacea, Amphipoda)

Abstract: Caprella mutica (Crustacea, Amphipoda) has been widely introduced to non-native regions in the last 40 years. Its native habitat is sub-boreal northeast Asia, but in the Northern Hemisphere, it is now found on both coasts of North America, and North Atlantic coastlines of Europe. Direct sequencing of mitochondrial DNA (cytochrome c oxidase subunit I gene) was used to compare genetic variation in native and non-native populations of C. mutica. These data were used to investigate the invasion history of C. mutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…3). The high levels of COI genetic divergence ([13 %) between C. andreae's C A and C B is within the interspecific values obtained in this study between the congeneric species C. penantis and C. dilatata (Table 3), as well as those described for other marine peracarid crustaceans (Ashton et al 2008;Xavier et al 2009Xavier et al , 2011.…”
Section: Taxonomic Issuessupporting
confidence: 56%
See 1 more Smart Citation
“…3). The high levels of COI genetic divergence ([13 %) between C. andreae's C A and C B is within the interspecific values obtained in this study between the congeneric species C. penantis and C. dilatata (Table 3), as well as those described for other marine peracarid crustaceans (Ashton et al 2008;Xavier et al 2009Xavier et al , 2011.…”
Section: Taxonomic Issuessupporting
confidence: 56%
“…They have been found to survive transport in ballast tanks (Carlton 1985) as well as dispersing over large distances as part of the fouling communities of sea-going vessels Astudillo et al 2009). In fact, the global distribution and introduction pathways of some invasive caprellid species can be attributed to these vectors (Caprella californica: AMBS 2002; Caprella mutica: Takeuchi and Sawamoto 1998;Ashton 2006;Ashton et al 2008;Caprella scaura: Krapp-Schickel et al 2006;Martí-nez and Adarraga 2008;Guerra-García et al 2011). Therefore, rafting on vessels, providing frequent opportunities for long-distance dispersal, is likely to be an important anthropogenic dispersal mechanism in C. andreae, which may also account for its wide geographic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The few examples we are aware of that have a sample size of X15 and a haplotype diversity 40.99 come from the marine amphipod Caprella mutica (Ashton et al, 2008), a fig-pollinating wasp Ceratosolen sp. 1 (Lin et al, 2008), the brittle star Ophiothrix fragilis (Muths et al, 2009) and the intertidal gastropods Nerita plicata and Nerita albicilla (Crandall et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of haplotypes common to both Atlantic coastlines indicates transAtlantic transport routes and/or the same source populations. Non-native populations on the Pacific coast of North America are genetically distinct, indicating a route of introduction independent from that of the Atlantic (Ashton et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Carlton (1979) suggested that C. mutica arrived on the Pacific and Atlantic coasts of North America either as a result of numerous, indepen-dent cross-oceanic introductions with oyster spat, or from small-scale transport following its first introduction (Carlton 1996). Direct sequencing of mitochondrial DNA indicates that C. mutica was introduced to Europe either directly from Asia or from the Atlantic coast of North America (Ashton et al 2008b). The presence of haplotypes common to both Atlantic coastlines indicates transAtlantic transport routes and/or the same source populations.…”
Section: Introductionmentioning
confidence: 99%